Internationalization of higher education in Vietnam: current situations, policies, and challenges. Issue 3 (14th July 2021) - Ryu, Jung Hyun; Nguyen, Anh Thuy
Abstract : Purpose: The research aims to provide the basis for a better understanding of the internationalization of higher education in Vietnam. First, it examines Vietnam's higher education reforms and policy/ legal frameworks for the promotion of internationalization since the implementation of Doi Moi in 1986. Secondly, it analyzes the internationalization activities at the national and institutional levels. At both levels, the internationalization activities are categorized into internationalization at home and cross borders (Knight, 2012). Finally, the paper discusses the challenges Vietnamese HE is facing and presents policy directions. Design/methodology/approach: This study employs a case study research strategy to examine and gain understanding of internationalization of higher education in Vietnam as a phenomenon. The study collected detailed information using a variety of data collection procedures over a period of time. First, it analyzes Vietnam's higher education reforms as well as policy and legal framework for the promotion of internationalization. Then, using Knight's framework, the study analyzed the internationalization at home and crossborder educational activities at the national and institutional levels. At the national level, strategic policy goals and programs were explored. Then, it chose Vietnam National University- Hanoi as a institutional case to learn its institutional strategies on cross border programs and mobility, reputation building, research cooperation. Findings: Vietnam has continuously reformed its legal and policy framework of higher education to better integrate into the global higher education market and also to meet the national demand for economic development. Predominant rationale for Vietnam to engage in crossborder programs is for brain development, specifically in the academics and public sector. Meanwhile internationalization at home is driven by (1) international programs and universities and (2) initiative to enhance competitiveness of its higher education institutes. Vietnam hosts different models of international universities, including classical, satellite and co-founded. However, issues and challenges remain, such as poor lack of systematic cooperation and coordination at the governmental level, retaining talents, and finally finances. Originality/value: Written for the special edition on Internationalization of Higher Education in the Era of SDGs: Asia–Pacific Perspective, the study aims to provide a basis for understanding the current situation of internationalization higher education in Vietnam and how it compares to its partners in the region. This study is unique as it provides a two-layer analysis, at the national and institutional levels capturing macro and micro perspectives in one scene. In addition, this study includes rich empirical data, which was rare in previous literature due to limited access.